Substitution, Augmentation, Modification and Redefinition (SAMR) Model to Improve Student's Critical Thinking Ability - Setiyawati, Sulis; Basori, Basori; Efendi, Agus (IJIE (Indonesian Journal of Informatics Education), 2023)
The use of technology in learning creates the need for applications and learning media that can improve students' critical thinking skills. The SAMR model (Substitution, Augmentation, Modification, and Redefinition), which offers teaching methods by integrating technology, can affect the learning process by improving students' critical thinking skills. This quantitative study used an experimental approach with a Posttest Only Control Design by dividing the sample into two groups (control and experimental classes) with cluster random sampling technique sampling on 54 students. The results of the post-test cognitive ability of the control class obtained an average value of 16.52, and in the experimental class, 19.63. Furthermore, the results of the post-test effective ability of the control class obtained an average value of 74.76 and in the experimental class of 84.07. This shows differences in students' critical thinking skills between students who use the SAMR model and those who do not use the SAMR model. In the results of the N-Gain analysis that has been carried out on the posttest value of the cognitive ability of the control class and the experimental class, the gain value of 0.33 is included in the medium criteria. While the N-Gain on the posttest value of the cognitive ability of the control class and the experimental class obtained a gain value of 0.19 which is included in the Low criteria. This study proves that the use of the SAMR model influences students' critical thinking skills, and the SAMR model has proven effective in improving students' critical thinking skills.